Menstrual Hygiene Practices of Adolescent Girls in Rural Maharashtra. (February 2021) - Aggarwal, Sumit; Ambalkar, Deepti; Madhumathi, Jayaprakasam; Badge, Vijay; Humne, Arun
Menstrual practices of adolescent girls in rural parts of India are greatly influenced by taboos and socio-cultural beliefs. In this study, the menstrual hygiene practices and beliefs of 122 adolescent girls between the ages of 13 and 19 years from rural Maharashtra were evaluated by personal interview and questionnaires. None of the girls had the right scientific knowledge about menstruation and were isolated during menstruation. They used cloth or home-made sanitary pads and were at risk of infections. There is a dire need for knowledge dissemination among school children and their families, increased awareness of menstrual hygiene and access to the requisite sanitary products in rural areas.